Status of certain serum biochemicals in the anorexic and ketotic bovines - SHARMA, I J; AGRAWAL, R G; JADIA, J K; QUADRI, M A (The Indian Journal of Animal Sciences, 2014)
The blood biochemical status of 52 advancect pregnant and postparturient anorexic and clinical ketotic cows and buffaloes, separately, were assessed. The blood glucose, plasma TVFA and oxaloacetate got reduced while pyruvate, lactate and ketone bodies got increased in the anorexic animals through ketosis. The degree of alteration in these blood parameters was higher in peak lactation. It was inferred that in the bovines the lactation ketosis is due to deficiency of energy, as treatment of such animals with propylene glycol restored back the blood parameters to normalcy.